Peran Ganda Ibu Dalam Pendidikan Anak di Saat Pandemi Covid-19 - Nadya Nurul Khairat; Junaidi Junaidi (Naradidik: Journal of Education and Pedagogy, 2022)
During the Covid-19 Pandemic, all learning activities are carried out online, all aspects of life become unstable, having implications for all aspects of human life, including the community's economy. Many heads of households have lost their jobs, and there are some heads of households who are unable to meet the needs of their families. Basically a housewife has duties in the family such as: serving her husband, raising children, cooking, cleaning the house and other general activities that are carried out like a housewife. But in reality many women, especially housewives, work to help their husbands to support their families. The theory used isThe role theory (role theory) was put forward by Stephen & Stephan. The research method used is qualitative with the type of case study. In this study, researchers selected informants by purposive sampling. The data analysis technique used is data analysis technique from Milles and Hurberman through analysis consisting of three activity lines, (1) reduction, (2) data presentation, and (3) conclusion drawing/verification.